A comparison of patients receiving vertebral body tethering for adolescent idiopathic scoliosis in the public and private hospital setting - Samuel Ng; Zhang Changmeng; Jason Cheung; Graham Ka Hon Shea (Journal of Orthopaedic Surgery and Research)
Abstract Purpose Vertebral body tethering (VBT) is a new growth-modulating surgery for adolescent idiopathic scoliosis (AIS) requiring a distinct skillset and intraoperative setup. We compared perioperative details and outcomes of VBTs performed in a public pediatric orthopedic hospital and a general private hospital setting. Methods We identified all patients receiving VBT for AIS from 1/2020 to 12/2023 with ≥ 6 months post-operative follow-up, with surgeries performed by the same senior surgeons. Clinical, radiological, and surgical details were retrieved. Results 24 VBTs were performed in the private setting and 16 in the public setting. Average age at operation was 11.9 ± 1.1 at a Sanders staging of 3.8 ± 1.2 when the major curve Cobb angle was 50.5 ± 8.0°. Tethered curves were most often thoracic in location (23/40) followed by thoracolumbar/lumbar curves (10/40) and double curve tethers (7/40). Overall correction ratio of 68.0 ± 19.0% was achieved. Time from booking to operation (82.2 ± 39.2 vs 63.1 ± 34.4 days, p = 0.112) and operation time (310 ± 86.4 min vs. 289 ± 87.4 min, p = 0.054) were longer in the public and private setting respectively but failed to reach statistical significance. Time to chest drain removal (1.5 ± 0.8 vs. 3.5 ± 1.7 days, p < 0.001) and length of stay (4.3 ± 0.9 vs. 6.6 ± 1.8 days, p < 0.001) were significantly shorter in the private setting, whilst complication rates remained similar (7/24 vs. 3/16, p = 0.456). Conclusion Expertise, resource availability, and costs differ in the public and private healthcare setting. With regards to VBT, the conditions for referral and surgical outcomes remained similar. Earlier drain removal and discharge for patients managed in the private setting was not associated with an increase in complication rate.